Lo scudo di Artemidora. Genere e formazione nell’“Amor di Marfisa” di Danese Cataneo - Artico, Tancredi (AOQU (Achilles Orlando Quixote Ulysses). Rivista di epica, 2022)
Focusing on the epic-chivalric poem Amor di Marfisa (1562) by Danese Cataneo, this article aims to investigate how the later epic tradition rewrites and reshapes the model of Ariosto concerning gender issues and the education of the heroine. Cataneo selects from Ariosto those narrative structures and literary themes useful for the definition of a canon of “virtù donnesca”, and reshapes them with classical myths, such as the myth of Lucretia. Marfisa and the newly invented character of Artemidora – the queen of Iceland, very similar to the original Bradamante – are two heroines-in-training: once they have completed their journey, they are destined to reach the highest degrees of feminine virtue, the virgin-queen and the married-queen. Concentrandosi sul poema epico-cavalleresco Amor di Marfisa (1562) di Danese Cataneo, il presente articolo mira a sottolineare gli aspetti della ricezione e dell’aggiornamento del modello ariostesco per quello che riguarda la questione di genere e la formazione dell’eroina. Cataneo recupera selettivamente l’eredità ariostesca, raccogliendo dal capolavoro gli spunti narrativi e tematici utili alla definizione di un canone della “virtù donnesca” e integrandoli con il repertorio della classicità, in particolare con il mito di Lucrezia. Marfisa e il personaggio di nuovo conio di Artemidora, regina d’Islanda e nuova Bradamante, sono due eroine in formazione, destinate a rappresentare – una volta compiuto il loro percorso – i gradi più alti della virtù femminile: la regina-vergine e la regina-sposata.